Analisis Sosiodemografis Pada Kesehatan Mental Ibu Dari Anak yang Belajar di Rumah Selama Pandemi COVID-19 - Miranda Rachellina; Asri Chasanah Adisasmita (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: The implementation of distance learning due to the COVID-19 pandemic has impacted not only the students but also parents especially mothers. This study was aimed to provide an overview of mothers’ mental health status (stress and anxiety) in Jabodetabek and its association with mother’s education level and occupation status, number of children, and number of children doing distance learning during the COVID-19 pandemic.Method: This was a cross-sectional study using an online questionnaire targeted to married women who have greater than 1 children in elementary school-high school doing distance learning in Jabodetabek. The data was collected in the period of 2-20 December 2020. Instruments used to measure stress and anxiety levels were PSS-10 and GAD-7.Results: There were 311 respondents aged between 27-61 years old. The average respondents had moderate stress and mild anxiety. The risk of severe stress increased significantly in mothers with elementary-middle education level (crude RR 2,1; 95%CI 1,04-4,4) and increased risk of moderate-severe anxiety in mothers with greater than 3 children (crude RR 1,9; 95%CI 1,1-3,1).Conclusion: More than 50% of mothers with children in elementary school-high school in Jabodetabek had moderate stress and 31% showed signs of mild anxiety. The mother’s sociodemographic factor associated with the risk of severe stress was education level. The factor associated with moderate-severe anxiety risk was the number of children living under one roof.